2022
DOI: 10.3390/nano12030351
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Thermal Stability and Optical Properties of Ultra-Small Nanodiamonds Synthesized under High Pressure

Abstract: Diamond properties down to the quantum-size region are still poorly understood. High-pressure high-temperature (HPHT) synthesis from chloroadamantane molecules allows precise control of nanodiamond size. Thermal stability and optical properties of nanodiamonds with sizes spanning range from <1 to 8 nm are investigated. It is shown that the existing hypothesis about enhanced thermal stability of nanodiamonds smaller than 2 nm is incorrect. The most striking feature in IR absorption of these samples is the ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 65 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, recent reports reveal that it can also be applied to investigate electrical conductivity in hydrogenated NDs. 57,58 The FTIR spectra of HPHT ND (Fig. 1c) and DND (Fig.…”
Section: Surface Chemistry and Structure Of Ndsmentioning
confidence: 99%
“…Interestingly, recent reports reveal that it can also be applied to investigate electrical conductivity in hydrogenated NDs. 57,58 The FTIR spectra of HPHT ND (Fig. 1c) and DND (Fig.…”
Section: Surface Chemistry and Structure Of Ndsmentioning
confidence: 99%
“…Such a finding is in good agreement with reports about hydrogenated nanodiamonds bearing an sp 2 ‐phase at their surface. [ 46,52,57,58 ] The Raman spectra recently reported by Mikesova et al on the same type of nanodiamonds depicted a significant amount of non‐ sp 3 carbon manifested by the presence of a pronounced G‐band and attributed to graphitic content in the case of HPHT ND‐ar. The purification of HPHT ND‐ar by air annealing considerably reduced the intensity of the non‐ sp 3 carbon band and there is only remaining isolated sp 2 carbon on HPHT ND‐O.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, the lattice defects and/or surface functional groups may influence the Raman signal. Since the BU_HPHT NDs in this study are monocrystals with excellent crystallinity (see the HRTEM images in the SI), we do not expect significant changes in the acoustic Raman modes caused by defects since X-ray fluorescence and FTIR spectroscopy showed that the surface of the BU_HPHT NDs is hydrogen terminated; i.e., the BU_HPHT NDs can be considered as “ligand-free” …”
Section: Resultsmentioning
confidence: 99%
“…Since the BU_HPHT NDs in this study are monocrystals with excellent crystallinity (see the HRTEM images in the SI), we do not expect significant changes in the acoustic Raman modes caused by defects since X-ray fluorescence and FTIR spectroscopy showed that the surface of the BU_HPHT NDs is hydrogen terminated; i.e., the BU_HPHT NDs can be considered as "ligand-free". 46 Figure 2 shows the low-frequency features of the 1.2−2.6 nm samples. The data were obtained by 442 and 633 nm excitations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%